The Effect of Game-Based Learning Media Word Square "Pena" On Increasing Knowledge of Diabetes Mellitus in SMK N 4 Yogyakarta Students - Sitanggang, Maria Frsikila Sitanggang; Khasanah, Furaida; Mardalena, Ida; Harmillah (International Conference on Health Sciences, 2026)
Background: The Indonesian Medical Association reported in January 2023 that cases of diabetes among adolescents had increased 70-fold. Efforts are made to increase knowledge through game-based learning media. The learning media used is Word Square "PENA". Objective: To analyse the effect of Word Square "PENA" on diabetes mellitus knowledge among students of SMK N 4 Yogyakarta. Methods: This research is a quasi-experimental research using an equivalent control group design. The sampling technique used was simple random sampling. The samples used were students of SMK N 4 Yogyakarta, totalling 98 respondents, consisting of experimental and control groups. Statistical tests using the Wilcoxon signed rank test and the Mann-Whitney. Results: This study shows that 59.2% of respondents were in the poor knowledge category of diabetes mellitus based on the pre-test results. After being given education using the Word Square "PENA", their knowledge increased by 71.4%, moving to the high category. Statistical test results show p-value = 0.000 (P< 0.05). To determine the effect of the Word Square "PENA" on the knowledge of diabetes mellitus among students of SMK N 4 Yogyakarta. Conclusion: The interactive learning media Word Square "PENA" is recommended as a strategic innovation in diabetes prevention education in schools, especially for the digital generation, which needs adaptive and fun learning methods.